MODEL PEMBELAJARAN PROBLEM BASED LEARNING MOTIVASI BELAJAR DAN PENINGKATAN PRESTASI BELAJAR MATA PELAJARAN EKONOMI SMA - Supandi Supandi (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
Education is system which have components, those are closely have related each other’s between teachers, students, curriculum, facilities, and infrastructure. The Purpose of study is to improve learning motivation and critical thinking skills of students specialization of social sciences on economic subject competence market basis Indonesia common stock exchange by emplementing of Problem-Based Learning model’s.The collecting data of this study was conducted by (1) observation, (2) the questionnaire, (3) study the documentation, and (4) the interview. The sample of this study took 4 class XI IPS specialization with a total of 114 at SMAN 2 Malang. Before the Questionnaire used for instrument of this study, it is validated to 30 students/leaners.In this case, the step which is used in learning model Problem Nased Learning (PBL) are (1) Oriented students on the problem, (2) Organize the student to learn, (3) To lead investigation of individual and group, (4) Develop and present the result work, and (5) To analyze and evbaluate the problem solving process (Dewey in Ibrahim, al.2005; 5)The results showed: 1) There are differences between mean learning students achievement Economics subjects and the implementation of Problem Based Learning model of learning between students who have high motivation to learn with students who have a low learning motivation (21.25 and 17.65), 2) There are differences in mean achievement Economics study subjects with the application of learning Problem Based learning to have a high motivation to learn (21.25 and 17.41) 3) There is no difference between the mean achievement of Economics study subjects with the application of learning Problem Based learning and motivation learners are low (17.65 and 15.67) 4) There is no difference between the mean achievement of Economics study subjects using Problem Based learning model of teaching and learning motivation is high (17.41 and 15.67). The conclusion of this study is implementing of learning model Problem Based Learning and the high motivation of learners / students can improve their critical thinking skills of learners and can improve performance significantly learning economy learners.